Strategia społecznej odpowiedzialności przedsiębiorstwa - Jakubów, Leon (Corporate Social Responsibility Strategy, 2008)
People expect more social and ecological responsibility from businesses. In response companies undertake philanthropic activities and prepare social audits. However, the most effective way is to combine the company's business interest with social needs, and this way giving it a strategic dimension.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 114-121